2004
DOI: 10.1111/j.1349-7006.2004.tb03229.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional gene silencing utilizing the lac repressor reveals a role of SHP‐2 in cagA‐positive Helicobacter pylori pathogenicity

Abstract: RNA interference (RNAi) is a newly described biological phenomenon mediated by small interfering RNA (siRNA) that targets mRNA for degradation by cellular enzymes and has become a powerful method for studying gene functions in mammalian systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…Higashi et al [22] have also found that ERK is activated by CagA via SHP-2 recruitment and activation in AGS cells. Similarly, CagA expression in gastric epithelial cells results in sustained ERK MAP kinase activation [23]. The research of Zhu et al [24] further confirms that the transformation of immortalized gastric epithelial cells is induced by CagA via the ERK/MAPK pathway.…”
Section: Discussionsupporting
confidence: 55%
“…Higashi et al [22] have also found that ERK is activated by CagA via SHP-2 recruitment and activation in AGS cells. Similarly, CagA expression in gastric epithelial cells results in sustained ERK MAP kinase activation [23]. The research of Zhu et al [24] further confirms that the transformation of immortalized gastric epithelial cells is induced by CagA via the ERK/MAPK pathway.…”
Section: Discussionsupporting
confidence: 55%
“…In this study, we used a pair of isogenic strains (147A and 147C) with identical CagA proteins, differing only by the presence of a single C-EPIYA motif (31)(32)(33) to elucidate the mechanisms by which tyrosine-phosphorylated CagA affects signaling within gastric epithelial cells. Because the C-EPIYA ؉ (phosphorylated) CagA (from 147C) has greater binding affinity to SHP2, as shown previously (23,34,36) and confirmed in our co-immunoprecipitation experiments, the extent of this interaction could affect downstream signaling pathways. For example, SHP2 positively regulates ERK activity, which is necessary for CagA induction of the hummingbird phenotype (23).…”
Section: Discussionmentioning
confidence: 64%
“…Expression Vectors-SHP2-specific small interfering RNA (siRNA) (kindly provided by Prof. M. Hatakeyama) was used to silence the expression of SHP2 (34). To selectively knock down human SHP2 expression, AGS cells were co-transfected with pSUPER-SHP2 and pBabePuro.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we next examined the effect of CagA on FAK tyrosine phosphorylation in AGSderived G11 cells, which stably express SHP-2-specific siRNA and thus show a marked reduction in SHP-2 expression (22). Notably, the level of FAK tyrosine phosphorylation was significantly elevated in G11 cells compared with the level in parental AGS cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AGS human gastric epithelial cell and AGSderived stable transfectant clone G11, in which SHP-2 was constitutively knocked down by SHP-2-specific small interfering RNA (siRNA) (22), were cultured in RPMI 1640 medium supplemented with 10% fetal bovine serum. Expression vectors were transiently transfected into AGS cells by using Lipofectamine 2000 reagent (Invitrogen) as per the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%